De l’autre côté du monde : langues véhiculaires et communication interethnique dans l’océan Indien à l’époque de la découverte portugaise - Luís Filipe Thomaz (Mélanges de la Casa de Velázquez, 2015)
When they reached the Indian Ocean in the 15th century, the Portuguese resorted chiefly to Arabic as a means of communicating with local authorities. A number of them were familiar with Arabic since Portugal had been occupying strongholds on the Moroccan coast. Having swiftly discovered that the language of Indian culture was Persian rather than Arabic, some Portuguese learned that tongue, thus facilitating diplomatic contacts in India and beyond. The language of trade in South-East Asia was Malay, which was used as far as the coasts of China. Portuguese then began gradually to expand throughout the Indian Ocean until it became a vehicular language alongside Malay. In the 17th century it supplanted Malay in that role, and several treaties between the English or the Dutch and local potentates were actually drafted in Portuguese. Other vehicular languages played a more minor role, for example Swahili on the East African coast or Tetum in Timor.